1998
DOI: 10.1159/000027285
|View full text |Cite
|
Sign up to set email alerts
|

Early Lens Changes Seen in Patients with Atopic Dermatitis Applying Image Analysis Processing of Scheimpflug and Specular Microscopic Images

Abstract: In order to know the initial lens changes that accompany atopic dermatitis (AD), 99 patients diagnosed dermatologically to have AD without any or with slight external ocular inflammations and with no habit of rubbing the eyelid due to severe itching were examined opthalmologically. Clinically, none of them showed any cataractous changes in their eyes. For the sake of comparison with the above population, 4 AD patients with cataractous eyes, 49 renal transplantation patients who were administered steroids over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 5 publications
(5 reference statements)
0
13
0
1
Order By: Relevance
“…This may be attributed to the persistence ASC is characterized by a prominent anterior subcapsular fibrotic plaque derived from the lens epithelial cells through the process of EMT (81)(82). ASC has been normally associated with conditions involving ocular inflammation or injury, such as in atopic dermatitis, uveitis and ocular surgery (83)(84)(85)(86), and numerous studies have implicated TGFβ in its pathogenesis (56,87). Similar to what we report for this study, others have shown TGFβ-induced subcapsular plaques in the lens to be primarily comprised of spindle-shaped contractile myofibroblastic cells, reactive for α-sma and embedded in excessive accumulations of ECM (57,64,70,(87)(88)(89)(90).…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the persistence ASC is characterized by a prominent anterior subcapsular fibrotic plaque derived from the lens epithelial cells through the process of EMT (81)(82). ASC has been normally associated with conditions involving ocular inflammation or injury, such as in atopic dermatitis, uveitis and ocular surgery (83)(84)(85)(86), and numerous studies have implicated TGFβ in its pathogenesis (56,87). Similar to what we report for this study, others have shown TGFβ-induced subcapsular plaques in the lens to be primarily comprised of spindle-shaped contractile myofibroblastic cells, reactive for α-sma and embedded in excessive accumulations of ECM (57,64,70,(87)(88)(89)(90).…”
Section: Discussionmentioning
confidence: 99%
“…The crater-like degenerative lesions were located at the basal-side membrane of the lens epithelium. It was concluded that the spots showed age-related or cataract changes of the basal side membrane of the epithelium [19,20]. Recently, the large black spots have strongly been suggested to be either areas of extremely flattened and aged squamous epithelium or to be infrequent small areas devoid of epithelial cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, using a slitlamp and a conventional specular microscope, in vivo LECs have only been observed on the surface of an intraocular lens and near the rim of the anterior capsular opening after cataract surgery [12][13][14]. The specular images of LECs in the crystalline lens in vivo were not well visualized when they were compared with those of corneal endothelial cells [15][16][17][18][19][20]. Recently, the new noncontact, autofocus specular microscope and the image analysis technique allowed us to clarify cellular borders and to obtain better specular images of LECs in vivo [21][22][23], and it is now possible to calculate the cell density and morphological features in these specular images.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of ASC is associated with several conditions [Marcantonio et al, 2003] involving trauma [Tang et al, 2003] or infl ammation and irritation of the eye, as occurs in atopic dermatitis [Sasaki, 1998;Brandonisio et al, 2001], which are all conditions associated with altered levels of TGF ␤ expression or activation. Interestingly, ASC is more prevalent in Asia, particularly Japan and Singapore [Sasaki et al, 2001] than it is in western societies [Deane et al, 1997;Marcantonio et al, 2003].…”
Section: Tgf ␤ -Induced Emt: a Model Of Anterior Subcapsular Cataractmentioning
confidence: 99%